Effective and Efficient Spawning Techniques of Koi Goldfish - Adris Robinson Dai; Rully Tuiyo; Syamsuddin Syamsuddin (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2020)
This study aims to determine effective and efficient koi fish spawning techniques and to determine the reproductive stages and fish behavior during spawning, as well as to identify problems in the spawning process. The procedure of this research consists of several stages, namely: Spawning Container Preparation, Parent Selection, Parent Release, Spawning Process, Quality of Spawning Water, Egg Counting. The results showed that natural spawning techniques were more effective and efficient. The size and weight of the fish are very influential for the number of eggs to be produced. One of the factors that support the success of a spawning is the selection to get good quality broodstock resulting in a high number of seed production. Keywords: koi; spawning; effectivity; efficiency.